Membangun Literasi Kesehatan Mental Siswa dalam Perspektif Hukum ( Sosialisasi Abdimas di SMA Negeri 1 Pangkah Kabupaten Tegal) - Soesi Idayanti; Moh.Taufik; Sugiyanto Sugiyanto; Moh Khamim (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Education is not only about academic knowledge, but also about the overall balance between body and mind. Amidst increasing academic demands and constant social pressures, students’ mental health is a crucial aspect that should not be ignored. Mental health literacy in a legal perspective is the foundation for academic success, healthy social interactions and overall quality of life. In the educational environment, we often talk about achievement, grades and preparation for the future, but we often forget that students’ mental health is an important foundation for achieving such success. Mental health disorders such as anxiety, depression or stress that are not addressed can interfere with concentration in learning, healthy social interactions, and even general physical health. Therefore, it is important for us to start building mental health literacy in a legal perspective among students. By knowing the symptoms that may appear, preventive measures that can be taken and available sources of support, we can help create an inclusive, caring and supportive educational environment for students’ mental well-being. Many countries have specific regulations that cover aspects of mental health literacy in the educational environment, including students’ rights related to access to services and protection from discrimination. Student mental health literacy from a legal perspective involves the application of legal principles in the context of protecting and fulfilling students' rights related to mental health in the educational environment. Mental health literacy from a legal perspective as an integral part of individual well-being is gaining increasing emphasis in the legal realm. Protection of individual mental health does not only rely on medical aspects, but is also closely intertwined with the rights and regulations that accompany it. Education, advocacy, and cross-sector collaboration are key in efforts to improve mental health protection from a legal perspective that includes interrelated social, educational, health, and legal aspects. Through a better understanding of this background, regulations and policies can be developed to better protect and support students' mental health in educational institutions.